Experimental Analysis of the Influence of Structural Parameters on the Behavior of Glass-Fiber Reinforced Polypropylene Composites - Bounouas, L.; Benmedakhene, S.; Laksimi, A.; Neumann, F.; Imad, A.; Azari, Z. (Проблемы прочности, 2001)
In a composite material reinforced by short
random fibers, damage results from different
elementary failure mechanisms such as matrix
micro-cracking, fiber pull out, failure of
fiber/matrix interface, failure of fibers, etc.
These damages have a large influence on the
macroscopic behavior of composite materials.
To obtain a good mechanical performance of a
composite material, it is important to optimize
the fiber ratio and the quality of the
fiber/matrix interface, which have a direct
influence on the damage mentioned above. The
main objective of this study is to determine the
influence of structural parameters on the
evolution of damage for two types of polypropylene
glass-fiber reinforced composites. In
parallel with a classical approach of the
mechanical theory of damage, which consists in
load-unload tensile tests, the use of acoustic
emission allows one to follow in real time the
character and the importance of damage
mechanisms in the course of loading. In
addition, fractographic analysis makes it
possible to confirm different assumptions and
conclusions from this study. В композитном материале, армированном случайно расположенными короткими волокнами,
повреждения при механическом нагружении возникают в результате действия разных
элементарных механизмов, таких как микрорастрескивание матрицы, выдергивание волокон,
разрушение межфазной границы волокно-матрица, разрушение волокон. Эти повреждения
оказывают большое влияние на макроскопические свойства композитного материала.
Для получения приемлемых механических характеристик композитного материала важно
оптимизировать концентрацию волокон, а также качество межфазной границы волокно-
матрица, которые оказывают непосредственное влияние на перечисленные выше повреждения.
Главной целью статьи является определение влияния структурных параметров на
эволюцию повреждаемости двух типов стеклопластиков на основе полипропилена. Одновременно
с классическим подходом к механической теории повреждаемости, основанной на
испытаниях на растяжение с периодической разгрузкой, использование метода акустической
эмиссии дает возможность изучать в реальном времени природу и важность
механизмов повреждений в процессе нагружения. В дополнение к этому фрактографический
анализ позволяет подтвердить различные предпосылки и заключения настоящего исследования. У композитному матеріалі, що армований випадково розташованими короткими
волокнами, пошкодження при механічному навантаженні виникають
внаслідок дії різних елементарних механізмів, таких як мікророзтріскування
матриці, висмикування волокон, руйнування міжфазової границі волокно-
матриця, руйнування волокон. Ці пошкодження зумовлюють значний вплив
на макроскопічні властивості композитного матеріалу. Щоб отримати прийнятні
механічні характеристики композитного матеріалу, важливо оптимі-
зувати концентрацію волокон, а також якість міжфазової границі волокно-
матриця, які безпосередньо впливають на ці пошкодження. Головна мета
роботи - визначення впливу структурних параметрів на еволюцію пошкодження
двох типів склопластиків на основі поліпропілену. Одночасно з
класичним підходом до механічної теорії пошкодження, що заснована на
випробуваннях на розтяг із періодичним розвантаженням, використання
методу акустичної емісії дає змогу вивчати в реальному часі природу і
важливість механізмів пошкоджень у процесі навантаження. Додатково до
цього фрактографічний аналіз дозволяє підтвердити різні передумови і
висновки даного дослідження.